Nursing Home in Medan City Using a Healing Environment Approach - Firman Eddy; Ridho Rahman (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Elderly is an integral part of the human life cycle. Basically, every individual will experience the stage of old age after going through childhood, adolescence and adulthood. In the elderly phase, the human body slowly experiences a decline in function, which is an early sign of the aging process. The plan for this nursing home aims to be a place for the elderly to gather with their community, preventing them from feeling lonely or neglected. The implementation of the Healing Environment concept also influences the elderly's experience of enjoying old age, involving architecture that integrates healing systems from nature, the five senses and psychological aspects.